Communication Theory - IM63 - 202102 - Cruz Cuevas, Martha Alejandra (2021)
This online course introduces you to the theories, ideas, and ways of knowing that are commonly used in the study of human communication. You will learn to identify your assumptions about knowledge, think about communication behavior in theoretic terms, use logic and reason, and evaluate ideas according to accepted criteria. You will also exercise your ability to write in English clearly and critically.